(untitled) (Heritage, 2024)
The study delves into the exploration of love themes and motifs within the late medieval Serbian adaptation of the Alexander Romance (14th century). It provides a comparative analysis of Alexander’s portrayal across different versions of the legend, beginning with the redaction (3rd century AD), where the king was depicted as an asexual hero. Progressing through the ε variant (7th–8th centuries), which presented the king as a gracious friend to his commanders, the focus eventually shifts to the Serbian Alexander Romance. In this adaptation, Alexander is portrayed as a lovesick, heterosexual knight, influenced by the Ovidian ideas prevailing in the late medieval period. Using the methods of Eve Kosofsky Sedgwick and Megan Moore, the study examines the ideological and poetic dimensions of Love within the Serbian Alexander Romance, highlighting its homosocial and thanatological characteristics. A comparative lens extends to late Byzantine literature, especially the Byzantine Achilleid. The conclusion drawn is that the late medieval Alexander Romance signifies the final instance of distorting the ancient genre of the classical love novel. The overarching theme in the ancient legend of the Greek king consistently revolves around the hero’s deification and death. Within this narrative, absolute Love (fin’amor) cannot be fully celebrated.